2020
DOI: 10.1111/tri.13612
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cell inhibition in a costimulation blockade‐based regimen for vascularized composite allotransplantation using a nonhuman primate model

Abstract: Vascularized composite allotransplantation (VCA) is challenged by the morbidity of immunosuppression required to prevent rejection. The use of highly specific biologics has not been well explored in VCA. Given that psoriasis is T-cell mediated, as is rejection of skin-containing VCAs, we sought to assess the role of ustekinumab and secukinumab, which are approved to treat psoriasis by inhibiting Th17 cells. We combined these agents with belatacept and steroids in a VCA nonhuman primate model. Group I consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Currently, belatacept seems as a promising agent that prolongs the rejection free survival when added to tacrolimus in experimental VCA models ( 38 ). However, belatacept in combination with steroids alone failed to prevent acute rejection and resulted in an average rejection free survival (time from transplant to early signs of rejection) of 10 days compared to an average rejection free survival 31.1 days in animals treated with tacrolimus, MMF and steroids ( 93 , 105 ). As it has been shown by us and others, the use of belatacept resulted in inhibition of DSA formation ( 39 , 93 ).…”
Section: Belatacept In Vca: Advantages and Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Currently, belatacept seems as a promising agent that prolongs the rejection free survival when added to tacrolimus in experimental VCA models ( 38 ). However, belatacept in combination with steroids alone failed to prevent acute rejection and resulted in an average rejection free survival (time from transplant to early signs of rejection) of 10 days compared to an average rejection free survival 31.1 days in animals treated with tacrolimus, MMF and steroids ( 93 , 105 ). As it has been shown by us and others, the use of belatacept resulted in inhibition of DSA formation ( 39 , 93 ).…”
Section: Belatacept In Vca: Advantages and Limitationsmentioning
confidence: 98%
“…However, belatacept in combination with steroids alone failed to prevent acute rejection and resulted in an average rejection free survival (time from transplant to early signs of rejection) of 10 days compared to an average rejection free survival 31.1 days in animals treated with tacrolimus, MMF and steroids ( 93 , 105 ). As it has been shown by us and others, the use of belatacept resulted in inhibition of DSA formation ( 39 , 93 ). As anticipated and similar to other organ transplants graft vasculopathy and antibody mediated rejection in VCA are associated with the presence of DSA or C4d deposits ( 106 110 ).…”
Section: Belatacept In Vca: Advantages and Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Wachtman et al (40) first evaluated the efficacy of combination CTLA4-Ig + tacrolimus compared to tacrolimus alone in a Yucatan miniature swine model and found that the addition of CTLA4-Ig significantly increased survival of grafts from a mean of 31 days to > 150 days. Atia et al (41) hypothesized that the addition of Th17 blockade to a CoB based regimen would limit T cell infiltration and may prolong graft survival. Treatment with ustekinumab (anti-IL12/23) and secukinumab (anti-IL17A) was shown to decrease skin T cell infiltration and expression of IL17A but was not associated with prolonged graft survival.…”
Section: Costimulation Blockadementioning
confidence: 99%
“…These include direct recognition of widely distributed donor MHC molecules on passenger leukocytes. These, combined with ubiquitous reperfusion events, plausibly allow for peripheral antigen presentation by activated non‐professional antigen‐presenting cells (APCs) such as vascular endothelium [7,8]. Additionally, heterologous immunity provides mechanisms by which cells primed via prior conventional protective immune mechanisms can undergo anamnestic activation to novel alloantigens without the need for a de novo priming event.…”
Section: Introductionmentioning
confidence: 99%